2020
DOI: 10.1007/s10815-020-01814-6
|View full text |Cite
|
Sign up to set email alerts
|

KIR and HLA-C genes in male infertility

Abstract: Purpose Approximately 50% of men reporting to clinics for assisted reproduction have abnormal sperm parameters; we therefore considered whether they differ from fertile males in terms of the frequency of KIR and HLA-C genes, suggesting the involvement of NK cells and some T cells in the inflammatory reaction that can occur in the testes, vas deferens, or epididymis. Method We tested a total of 1064 men: 445 of them were patients who, together with their female partners, participated in in vitro fertilization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Genomic DNA was isolated from venous blood using the Invisorb Spin Blood Midi Kit (Invitek, Germany) or QIAamp DNA Mini Kit (Qiagen, Germany) according to the manufacturer's instructions. KIRs were genotyped using KIR Ready Gene kits (Inno-train Diagnostics, Germany) following the manufacturer's instructions [for details, see reference (42) and Table 2)] or multiplex PCR described elsewhere (43,44). Our KIR typing was validated three times per year by the International KIR Exchange program organized by the Immunogenetics Center of the University of California, Los Angeles.…”
Section: Dna Preparation and Genotypingmentioning
confidence: 99%
“…Genomic DNA was isolated from venous blood using the Invisorb Spin Blood Midi Kit (Invitek, Germany) or QIAamp DNA Mini Kit (Qiagen, Germany) according to the manufacturer's instructions. KIRs were genotyped using KIR Ready Gene kits (Inno-train Diagnostics, Germany) following the manufacturer's instructions [for details, see reference (42) and Table 2)] or multiplex PCR described elsewhere (43,44). Our KIR typing was validated three times per year by the International KIR Exchange program organized by the Immunogenetics Center of the University of California, Los Angeles.…”
Section: Dna Preparation and Genotypingmentioning
confidence: 99%
“…KIR receptors play an important role in the control of NK cell function. They are receptors present on the surface of natural cytotoxic cells and certain subpopulations of T cells: γδ, αβ, CD8+, and CD4+ [ 61 , 62 , 63 ]. Because both KIR receptors and MHC class I antigens are highly polymorphic, their interactions differentiate and individualize the NK cell response [ 64 ].…”
Section: Structure Of Kir Receptorsmentioning
confidence: 99%
“…Fertile men differ in their KIR gene profile and KIR–HLA-C combinations from men entering IVF treatment. Potential integrations between activating KIR receptors in CenAB + BB carriers and HLA-C allotypes may influence male infertility, while carriers of the KIR CenAA genotype do not experience problems with conception [ 61 ].…”
Section: Research Reviewmentioning
confidence: 99%
“…Regarding more Specifically, different alleles of the HLA-B gene have been associated with autoimmune diseases (such as HLA-B27 and its relationship with psoriatic arthritis and In the reproductive field, the HLA antigens have been demonstrated to be crucial for the embryo-maternal tolerance and the achievement of a successful pregnancy (Chattopadhyay et al, 2014;Tersigni et al, 2020). For instance, some molecules as the high polymorphic HLA-C participate in the innate immune system by serving as a ligand for the inhibitory killer cell immunoglobulin-like receptors (KIRs) present on natural killer (NK) cells (Leone et al, 2013;Wilczyńska et al, 2020). HLA-C (along with the HLA-E, G and F ones) from both maternal and paternal origin is highly expressed by the extravillous trophoblasts invading the uterine tissues.…”
Section: Hla-b Genementioning
confidence: 99%
“…A recent study has shown that women affected with MS had lower live birth rates (LBR) compared to unaffected women (irrespective of their infertility diagnosis or treatment) (Houtchens et al, 2020). This statistically significant difference in LBRs was more evident in women in early (Bauer-Mehren et al, 2011;Profaizer and Eckels, 2012;Leone et al, 2013;Chattopadhyay et al, 2014;Mosaad, 2015;Pinero et al, 20152015;Robinson et al, 2015;Piñero et al, 2017;Wieczorek et al, 2017;Jongsma et al, 2019;Piñero et al, 2020;Tersigni et al, 2020;Wilczyńska et al, 2020) and middle (Emmery et al, 2016;Nielsen et al, 2017;Agius et al, 2018;Papúchová et al, 2019) childbearing years. The difference between women with and without MS disappeared after receiving infertility treatments, thus highlighting the importance of information regarding the efficacy of infertility treatments in women with autoimmune diseases (Houtchens et al, 2020).…”
Section: Experimental Autoimmune Encephalomyelitismentioning
confidence: 99%